Drain fluid amylase in defining clinically relevant postoperative pancreatic fistula following pancreaticoduodenectomy: day 5 is better than day 3 - Vutukuru, Venkatarami Reddy; Gavini, Sivarama Krishna; C., Chandramaliteeswaran; A., Dinakar Reddy; Dasari, Varun; Settipalli, Sarala (International Surgery Journal, 2017)
Background: Postoperative pancreatic fistula (POPF) remains the most serious complication of Pancreaticoduodenectomy. ISGPF defined POPF in 2005 based on drain fluid amylase on or after day 3 and graded the severity. But as Grade A fistulas are not clinically relevant, most of the clinicians do not consider them as POPF. Hence exact incidence of POPF is not known. Our aim is to see weather drain fluid amylase on or after day 5 can define clinically relevant POPF better than day 3. Methods: Prospective study included all patients who underwent Pancreaticoduodenectomy during the period January 2013 to November 2016. Serum and Drain fluid amylase were analyzed on Day 3. Those who met criteria of POPF underwent repeat amylase on Day 5. These patients were divided into 2 groups. Group A includes patients whose Day 5 amylase normalized and Group B where elevated Amylase persisted. Outcomes were compared in 2 Groups in terms of clinically relevant POPF (CRF), DGE, Haemorrhage (PPH), hospital stay and 30 Days mortality. Results were analysed and p value <0.05 was considered significant. Results: On 110 patients, 44 (40%) met ISGPF criteria of POPF. Of 44, 36 (82%) had normalized Amylase on Day 5 (Group A). Only 8 (18%) had persistent elevated amylase (Group B). None in Group A had CRF, whereas in Group B, 6(75%) had CRF and 2(25%) had only biochemical leak (p<0.0001). DGE was significantly higher in Group B (87.5% vs. 33.3%; p=0.013). PPH was seen in only 1 patient (Group A). Duration of hospital stay and 30day mortality were similar. Conclusions: Drain fluid amylase levels on or after Day 5 defines clinically relevant POPF better than levels on or after day 3.